The Use of Diatomite to Remove Color and Turbidity in Sugar Industry - Ladda Meesuk; Atthawan Benjamas; Cherdsak Utha-aroon (Agriculture and Natural Resources, 2008)
Diatomite is a pale colored, light weight rock composed mostly of silica microfossil of algae, being known as diatoms. The experiments of using natural diatomite from Lampang, central Thailand to remove color and turbidity in sugar cane juice processed in a sugar factory gave satisfactory results. The color in ICUMSA (International Commission for Uniform Methods of Sugar Analysis) and turbidity of the treated juice were better, i.e., lower than that of the clarified juice from the industrial process lines, while sugar content tended to be higher. The two most appropriate conditions were obtained; when diatomite was used not more than 4% by weight of the juice or 2% diatomite followed by 1 ppm anionic polymer. Analyses of properties of the treated juice and physical and chemical properties of diatomite revealed physical and chemical adsorption properties of diatomite.